Phenytoin-induced increase in growth hormone response to levodopa in adult males. Issue 7 (July 1984) - D'Alessandro, R; Cortelli, P; Gallassi, R; Ghisoli, E; Montanaro, N; Zoni, E; Baruzzi, A
Abstract : Growth hormone and prolactin response to levodopa were evaluated before and after long-term phenytoin treatment in five men with previously untreated partial epilepsy. After phenytoin treatment, growth hormone response to levodopa increased. There was a close relationship between growth hormone response to levodopa and plasma phenytoin concentrations. These findings suggest a phenytoin-induced dopaminergic activity at the hypothalamic-pituitary level in adult males.